The “Flatness” of Deleuze and Guattari: Planning the City as a Tree or as a Rhizome? - Hillier, Jean (Taylor & Francis, 2021)
Flat ontology has become an umbrella term for several theoretically based approaches, notably Delanda’s controversial reconstruction of DeleuzoGuattarian concepts. I highlight key divergences in Delanda’s “flat ontology” from that of Deleuze and Guattari’s “flattening” of multiplicities on a plane of immanence. The rhizome is arguably the concrete image of Deleuze and Guattari’s multiplicity, constituted by intensive relations, or becomings, between heterogeneous singularities. A rhizomatic multiplicity contrasts markedly with the hierarchical dualism of the pseudomultiplicities of arborescent structures. Referencing Marston et al.’s “flat” site-ontology, I introduce sites as DeleuzoGuattarian event- spaces; emergent properties of entangled human and non-human relations and their capacities to affect and be affected. I select two spatial planning sites from urban fringe Australia, both of which involve significant transformation of (semi-)riparian habitat. One illustrates an arborescent system of thought and practice and the other a more rhizomatic approach which explores the situational potential of human/non-human encounters. I explore capacities of both sites to affect humans and non-humans and how the respective planning systems engage with them. I then question the possibility of rhizomatic planning practices, whether arborescence is inevitable, or whether a double-structure is possible, before concluding that a double-structure may afford glimpses of the bi-directionality or “flattening” of DeleuzoGuattarian multiplicity – “both/and” – an inclusive disjunctive synthesis of becoming.
Keywords: Planungstheorie; Planungspraxis; Raumbegriff; Planungsebene; Hierarchie; Fallstudie; Stadtrand; Stadtumland; Flache Ontologie; Mehrdimensionalität